دراسة میدانیة لریادة الأعمال النسائیة في منطقة الشرق الأوسط − التحدیات والفرص− - ضیف , عائشة; بوران , سمیة (Finance and Business Economies Review, 2017)
The primary aim of this research is to examine challenges and opportunities facing women entrepreneurship in the developing context of MENA region with a particular focus on sociocultural context of Algeria. While existing studies have laudably increased the interest of scholars in theorizing and conceptualizing issues and policy makers in promoting entrepreneurship in various economic sectors and for everyone, there has been a tendency to over emphasize male entrepreneurship with a particular focus on Anglo-American economies and a few emerging business contexts. Such Western- and male-dominated entrepreneurship research has been to the detriment of other: women entrepreneurship in non-Western developing economies which are characterized by their masculine domination. The absence of recent empirical research on women entrepreneurship suggests that the existing research of entrepreneurship fails to account for challenges and opportunities in contemporary fast-growing economies of MENA region which has been characterized by its unique socioeconomic, religious, cultural and political context. In fact, recent research evidence indicates that women entrepreneurship world wide is an under-tapped force that has the potential to rekindle economic growth and development in the region. Overall, the current study highlights a need for a context-based evaluation of women entrepreneurship. In the light of sparse nature of the empirical evidence on women entrepreneurship within the milieu of non-Western developing economies, the rise of feminism coupled with the promising economic opportunities for women in MENA region, the fundamental question remains as to ‘whether the current business environment promotes or inhibit female entrepreneurship in the region’. The current study aims to respond to this question by adopting a qualitative research method to elucidate the factors that could play a part in creating a robust business environment for women entrepreneurship in Algeria. In a manner consistent with the institutional theory, the findings lend support to myriad of institutional forces and social structure that impede transition to a stable business environment which is conducive to women entrepreneurship: the assumptions underpinning